That's not my monster-- : its nose is too bobbly - Watt, Fiona; Wells, Rachel (Tulsa, Okla. : EDC, 2004)
A little mouse searches for his monster based on the textures of his eyebrows, spikes, paws, horns, and ears.
Cover title.
On textured board pages.
1.7
K-3
Keywords: Mice -- Juvenile fiction; Monsters -- Juvenile fiction; Textured books -- Specimens; Toy and movable books -- Specimens; Mice -- Fiction; Monsters -- Fiction; Textured books; Toy and movable books; Mice -- Fiction; Monsters -- Fiction; Toy and movable books